The complexity of value in the luxury industry: From consumers' individual value perception to luxury consumption. Issue 10 (6th October 2015) - Hennigs, Nadine; Wiedmann, Klaus-Peter; Klarmann, Christiane; Behrens, Stefan
Abstract : Purpose: – In an attempt to satisfy the rising demand for luxury in the era of the "democratisation of luxury" or the "luxurification of society" without threatening the uniqueness and exclusivity of luxury brands, a profound understanding of the luxury concept and its deeper values is essential. As the complexity of luxury value and the assessment of effects on individual luxury value perception and related behavioral outcomes are still poorly understood and widely unexplored, the purpose of this paper is to fill this research gap. Design/methodology/approach: – In the exploratory study context of examining the antecedents and outcomes of individual luxury value perception, PLS path modeling was used for the empirical tests of the hypotheses. Findings: – The results support the assumption that the desire for luxury brands involves several dimensions of luxury value including financial, functional, individual and social consumer perceptions. Besides, the individual luxury value perception is significantly related to the consumption of luxury goods in terms of purchase intention, recommendation behavior and the willingness to pay a premium price. Originality/value: – The incremental value of the present study is to present and empirically verify a concept that embraces the complexity of luxury value and its causal effects on different aspects of luxury consumption. The results have important implications for luxury brand management and future research in the domain of luxury goods. By addressing the specific value aspects that are highly relevant for consumer loyalty to the brand, a luxury company can stimulate purchase behavior with appropriate marketing campaigns that create and preserve the most important value aspects throughout the supply chain from production to distribution.